Beyond the Pandemic: Decoding Shifts in Hotel Stay Intentions in Indonesia Post-COVID-19: Pasca Pandemi: Menguraikan Perubahan Keinginan Menginap di Hotel di Indonesia Pasca COVID-19 - Suzano, Ricky; Jayadi, Handi; Empi, Febi Raharja; Wijaya, Lianna; Wang, Wen (Institut Pariwisata dan Bisnis Internasional, 2024)
This study explores the factors influencing tourists' decisions to choose hotel accommodations during the COVID-19 pandemic, providing valuable insights into shifting consumer behavior. Employing a quantitative methodology, the research used an online survey targeting tourists in the JABODETABEK region, with 263 responses collected. Data were analyzed using Structural Equation Modeling via SMART PLS 3.0. The findings reveal that Perceived Threat negatively affects the intention to stay at hotels, while both Government Trust and Social Trust positively and significantly influence stay intentions. Interestingly, Customer Individual Response Efficacy and Hotel Response Efficacy do not show a significant effect on stay intentions. Additionally, Perceived Threat does not impact Government Trust, Social Trust, or Hotel Response Efficacy. However, Customer Individual Response Efficacy significantly enhances both Government and Social Trust, as well as Hotel Response Efficacy. The urgency of these findings lies in the critical need for hotels to rebuild consumer trust in the post-pandemic era. Trust in government and social institutions plays a pivotal role in shaping tourists' accommodation choices. This research offers novel insights into the evolving decision-making process of tourists, highlighting the importance of addressing public health concerns and fostering trust. The study contributes to the hospitality industry's strategies for ensuring long-term resilience and success by focusing on consumer trust and response efficacy. This research provides practical recommendations for hoteliers to adapt their approaches and navigate the complexities of a post-COVID-19 tourism landscape.